Improving the Therapeutic Efficacy of Sorafenib for Hepatocellular Carcinoma by Repurposing Disulfiram - Zhang, Gong; Wang, Yufeng; Fuchs, Bryan C.; Guo, Wei; Drum, David L.; Erstad, Derek J.; Shi, Baomin; DeLeo, Albert B.; Zheng, Hui; Cai, Lei; Zhang, Liyuan; Tanabe, Kenneth K.; et al. (Frontiers in Oncology, 2022)
Background. Sorafenib, a kinase inhibitor, is a standard treatment for advanced hepatocellular carcinoma (HCC) but provides only a limited survival benefit. Disulfiram (DSF), a drug for treating alcoholism and a chelator of copper (Cu), forms a complex with Cu (DSF/Cu). DSF/Cu is a potent inducer of autophagic apoptosis of cancer stem cells, which can demonstrate drug resistance. Thus, we hypothesized that DSF/Cu could increase the sensitivity of HCC cells to sorafenib by targeting hepatic cancer stem cells. Methods. The synergistic effect of DSF/Cu and sorafenib on human HCC cell lines was assessed by cell viability MTT assay. Changes in stemness gene expression in HCC cells were investigated by assessing the presence of hepatic cancer stem cells (HCSCs) (defined as ALDH+CD133+ cells) using flow cytometry, sphere formation ability as an index of in vitro tumorgenicity, and expression of stemness gene-encoded proteins by western blot. Autophagic apoptosis and the ERK signaling pathway were also assessed by western blot. Furthermore, the in vivo anti-tumor efficacy of DSF/Cu and sorafenib was tested using orthotopic HCC xenografts in mice. Results. Compared with sorafenib alone, DSF/Cu + sorafenib synergistically inhibited proliferation of all HCC cell lines, decreased the stemness of HCC cells, and increased the autophagy and apoptosis of HCC cells. The mechanism by which DSF/Cu mediated these phenomena with sorafenib was sustained activation of the ERK pathway. The combination of DSF/Cu (formed with endogenous Cu2+) and sorafenib was significantly more effective than sorafenib alone in inhibiting the growth of orthotopic HCC xenografts in mice. This in vivo anti-tumor efficacy was associated with decreased stemness in treated HCC tumors. Conclusions. DSF/Cu and sorafenib can synergistically and effectively treat HCC by targeting HCSCs in vitro and in vivo. Our data provide a foundation for clinical translation.